Interaction of simultaneous language processing and speech motor act in young stutterers - V, Nandakumar (Journal of All India Institute of Speech and Hearing)
This investigation was aimed at studying the hypothesis that "Language and speech motor processes may interfere with one another during the act of talking at least in children who are beginning to stutter" (Peters and Starkweather, 1990). Fifteen child stutterers and fifteen normal children in the age range of 6-9 years were investigated on three tasks specifically designed to test the following: i. Language and speech motor process interference, ii. Language and non-speech motor process interference, iii. Non-speech motor and cognitive process interference.